Advanced microgrid and its multi‐objective regulation strategy for shore supply. Issue 13 (19th January 2018) - Yu, Moduo; Huang, Wentao; Tai, Nengling; Zheng, Xiaodong; Ma, Zhoujun; Wang, Yong
Abstract : This study presents a new microgrid paradigm for the shore‐side power supply system. The shore supply microgrid is developed for container and cruise harbours to further improve the capability of energy saving and emission reduction. The typical structure and operation modes are designed based on the requirements of shore supply systems. A multi‐objective regulation strategy is devised for energy management system. The strategy aims to reduce power fluctuation and to implement the microgrid self‐supply at ports. A parallel optimisation model is built to solve the regulation problem. A study case of four different ship‐berthing scenarios is utilised to validate the effectiveness of the designed microgrid and its regulation strategy.